Application of Shaiful Bahri's Humour Model in the Shadow Puppet Theatre of Kelantan: (Aplikasi Model Humor Shaiful Bahri: Suatu Pembaharuan dalam Wayang Kulit Kelantan) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
This article discusses elements of himour in the wayang kulit-the shadow puppet theatre-of Kelantan, focusing especially on the performances of Dalang Saupi. As an increasingly sidelined art form, wayang kulit is becoming irrelevant as a form of entertainment due to its rigid elements of humour and its outdated style. In reaction to this, Dalang Saupi has carried out some modifications. In terms of its narrative, the humourous aspects of the inang or lady-in-waiting has been expanded and given greater prominence, apart from such characters as Pak Dogol, Said, Wak Long, Samat and Wok Yoh, which are made to seem more current. This field work study was carried out in Kota Bharu, Pasir Mas, Machang and Pasir Putih in Kelantan, and concerned itself with four storylines. The article explains how Dalang Saupi infuses humour in his performances, using Shaiful Bahri's (2000) humour model as a basis. Cricisim, oddness, strangeness and surprise are employed to attract audience attention and inject fresh life into the wayang kulit of Kelantan.Keywords: humour, Kelantanese shadow puppet theatre, criticism, oddness, strangeness, susprise